God, evil, and suffering in Islam - Sayilgan, Salih (Cambridge University Press, 2025)
"Examines the Islamic theological approaches to the problem of evil and suffering both in theory and practice. The study does not only engages with the themes of aging, sickness, and death, it also sheds light on contemporary questions such as disability, environmental crisis, and pandemics"--